Identifying genetic determinants of inflammatory pain in mice using a large-scale gene-targeted screen. Issue 6 (13th June 2022) - Wotton, Janine M.; Peterson, Emma; Flenniken, Ann M.; Bains, Rasneer S.; Veeraragavan, Surabi; Bower, Lynette R.; Bubier, Jason A.; Parisien, Marc; Bezginov, Alexandr; Haselimashhadi, Hamed; Mason, Jeremy; Moore, Michayla A.; et al.
Abstract : A reverse genetics screen of 110 single-gene knockout mouse strains identified 13 genes affecting nociception, including 10 that have no previous phenotypic associations with pain. Abstract: Identifying the genetic determinants of pain is a scientific imperative given the magnitude of the global health burden that pain causes. Here, we report a genetic screen for nociception, performed under the auspices of the International Mouse Phenotyping Consortium. A biased set of 110 single-gene knockout mouse strains was screened for 1 or more nociception and hypersensitivity assays, including chemical nociception (formalin) and mechanical and thermal nociception (von Frey filaments and Hargreaves tests, respectively), with or without an inflammatory agent (complete Freund's adjuvant). We identified 13 single-gene knockout strains with altered nocifensive behavior in 1 or more assays. All these novel mouse models are openly available to the scientific community to study gene function. Two of the 13 genes ( Gria1 and Htr3a ) have been previously reported with nociception-related phenotypes in genetically engineered mouse strains and represent useful benchmarking standards. One of the 13 genes ( Cnrip1 ) is known from human studies to play a role in pain modulation and the knockout mouse reported herein can be used to explore this function further. The remaining 10 genes ( Abhd13, Alg6, BC048562, Cgnl1, Cp, Mmp16, Oxa1l, Tecpr2, Trim14, and Trim2 ) reveal novel pathways involved in nociception and may provide new knowledge to better understand genetic mechanisms of inflammatory pain and to serve as models for therapeutic target validation and drug development.